Clinical Predictors of Long-Term Outcomes in Patients With Critical Limb Ischemia Who have Undergone Endovascular Therapy. (April 2014) - Chang, Shang-Hung; Tsai, Yueh-Ju; Chou, Hsin-Hua; Wu, Tien-Yu; Hsieh, Chien-An; Cheng, Shih-Tsung; Huang, Hsuan-Li
Clinical predictors of long-term outcomes in patients with critical limb ischemia (CLI) treated with endovascular therapy (EVT) remain unclear. In this study, clinical predictors of long-term outcomes in EVT-treated patients with CLI were investigated. In this prospective, observational study, we analyzed a total of 253 Taiwanese patients with CLI with 314 limbs who underwent EVT between 2005 and 2012. Cox models were used to estimate hazard ratios of death, limb loss, and sustained clinical success (SCS). Multivariate analysis showed that age, atrial fibrillation (AF), end-stage renal disease (ESRD), and albumin were significant predictors of mortality. Patients with coronary artery disease and low albumin levels had a significant risk of major limb amputation, while AF, ESRD, and albumin were significant, independent predictors of SCS. In addition to previously reported predictors, we showed that AF and malnutrition can be used to predict long-term outcome in EVT-treated patients with CLI.